(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To assess the outcome of collagen dressing in the treatment of diabetic foot ulcers.Materials & methods: 100 patients who presented with diabetic foot ulcers were included as study group. Patients with diabetic foot ulcers who were known cases of carcinomas and connective tissue disorders were excluded from the present study. Pre-treatment dimensions were recorded. Collagen dressing was applied at regular follow-ups and subsequent examination of the lesion was done.Results: Mean wound area before dressing as 41.3 mm2, while mean wound area second weak after dressing was 18.9 mm2. Significant results were obtained while comparing the mean wound area before dressing and second week after dressing.Conclusion: Diabetic foot ulcers treated with collagen dressing are efficacious in terms of reduction in wound area resulting in early wound healing. Collagen-based wound dressings can be an effective tool in the healing of diabetic foot wounds.